2017
DOI: 10.1093/ndt/gfw342
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for immunosuppression in immunoglobulin A nephropathy?

Abstract: The most common primary glomerular disease globally is IgA nephropathy (IgAN). It is often a slowly progressive disease, and ∼40% of patients will progress to kidney failure. Due to a lack of large clinical trial networks and a lack of surrogate markers of treatment efficacy, there are relatively few large multicenter clinical trials in IgAN. Given that both the pathogenesis and progression of IgAN are linked to defects in mucosal immune regulation and inflammation, use of immunosuppression to prevent kidney f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Considering a number of adverse effects, immunosuppression should be prescribed only for patients at the highest risk of developing ESRD [85]. Al-Lawati et al suggested that immunosuppressive drugs in IgAN ought to modulate immune responses, including Gd-IgA1 production, glomerular and tubulointerstitial inflammation, and mesangial and endothelial cell proliferation [85].…”
Section: T Cells As a Therapeutic Target Of Traditional And Biologicamentioning
confidence: 99%
“…Considering a number of adverse effects, immunosuppression should be prescribed only for patients at the highest risk of developing ESRD [85]. Al-Lawati et al suggested that immunosuppressive drugs in IgAN ought to modulate immune responses, including Gd-IgA1 production, glomerular and tubulointerstitial inflammation, and mesangial and endothelial cell proliferation [85].…”
Section: T Cells As a Therapeutic Target Of Traditional And Biologicamentioning
confidence: 99%
“…However, no recommendation was made for patients with eGFR < 45 ml/min/1.73m 2 . Given that some studies supported the use of steroids or immunosuppressants [7][8][9] for these patients, which is also widely applied clinically, thus we conducted this study to explore whether corticosteroids or immunosuppressant therapies could improve the renal outcome of patients with advanced IgAN (eGFR < 45 mL/min/1.73 m 2 and mean proteinuria > 1 g/24h).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it was found, that during the first six post-transplant months, the area under the receiver operating characteristic curve of prednisone was significantly associated with the decrease of Gd-IgA1 and IgA1, whereas area under the receiver operating characteristic curve of tacrolimus was associated with the decrease of IgA1 in the same period. A meta-analysis revealed that tacrolimus combined with low-dose glucocorticoids is an effective and safe therapeutic option for the treatment of IgAN in native kidneys as well [ 36 ]. Exploitation of tacrolimus in patients with refractory IgAN has also been tried with promising results [ 37 ].…”
Section: Discussionmentioning
confidence: 99%